ANALISIS SIKAP DAN PERILAKU PENGHEMATAN LISTRIK PADA SEKTOR RUMAH TANGGA - Yuliati, Lilik Noor; Djamaludin, Moh. Djemdjem; Sari, Anggi Mayang (Jurnal Ilmu Keluarga dan Konsumen, 2011)
Population growth and increasing of economic activity encourage the growth of electricity consumption in Indonesia. Saving electricity is one of the solutions to make a proper balance between the electricity supply and the electricity demand. This research was to analyze the correlation between attitudes and behaviour of saving electricity and the influences of internal factors, external factors, and attitudes toward behaviour of saving electricity in household sector at Bogor City. Households involved in this research were 113 households that were selected by proportional random sampling. Attitudes were measured from three aspects, were cognitive, affective, and conative. Data was collected by interview with questionnaire and was analyzed by descriptive, correlation test, and regression test. The research Results showed that attitudes (cognitive aspect) correlated significant with behaviour of saving electricity. Regression analysis showed that behaviour of saving electricity was influenced by electric power, lifestyle, the amount of information access, and attitudes (cognitive aspect).